1998
DOI: 10.1123/jsr.7.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Intertester and Intratester Reliability of a Dynamic Balance Protocol Using the Biodex Stability System

Abstract: Evaluating balance can be an important part of the rehabilitation protocol of an athletic injury. One purpose of this study was to determine the intertester and intratester reliability scores of single-leg stability on a platform of gradually decreasing stability using the Biodex Stability System (BSS). The second purpose was to determine intertester and intratester reliability scores of subject foot placement on the BSS. Subjects (N= 19) underwent a familiarization session on Day 1 that included five 30-s bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
115
0
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(127 citation statements)
references
References 5 publications
(3 reference statements)
2
115
0
10
Order By: Relevance
“…Intertester and intra-tester ICC stability scores ranged from .70 to .42 and .80 to .43, respectively [26]. Schmitz & Arnold [26] concluded that the BBS was a reliable tool for testing dynamic stability. The BBS DLOS system appeared to accurately and uniquely depict dynamic balance in both pathological and healthy populations.…”
Section: Biodex Balance System Dynamic Limits Of Stabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Intertester and intra-tester ICC stability scores ranged from .70 to .42 and .80 to .43, respectively [26]. Schmitz & Arnold [26] concluded that the BBS was a reliable tool for testing dynamic stability. The BBS DLOS system appeared to accurately and uniquely depict dynamic balance in both pathological and healthy populations.…”
Section: Biodex Balance System Dynamic Limits Of Stabilitymentioning
confidence: 99%
“…Hinman [27] suggested that dynamic balance testing using the BBS LOS test may have been too difficult for a participant population with pre-existing balance impairments as a percentage of test participants were unable to complete the DLOS tests without using upper extremity assistance to prevent complete loss of balance. Schmitz & Arnold [26] determined the intertester and intratester reliability values for the BBS DLOS for dynamic balance through a unilateral stance protocol based on anterior to posterior (A-P), medial lateral (M-L), and overall stability indices. Intertester and intra-tester ICC stability scores ranged from .70 to .42 and .80 to .43, respectively [26].…”
Section: Biodex Balance System Dynamic Limits Of Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…(23) Body balance was estimated with a postural sway platform (Biodex Stability System; Biodex Medical Systems, Shirley, NY, USA). (24) Body balance was expressed as a stability index, a unitless measure that reflect the variance of platform displacement from level. A high number indicates less motion control and poor postural stability.…”
Section: Measurementsmentioning
confidence: 99%